Методика проектирования тягового электрооборудования для электромеханических трансмиссий - Флоренцев, Станислав Николаевич (НТУ "ХПИ", 2014)
Рассматривается комплексный подход проектирования всех частей комплекта тягового электрооборудования ( КТЭО) для электромеханических трансмиссий различных транспортных средств - генераторов, тяговых двигателей, силовой и управляющей электроники. Проектирование проводится для реализации тягово-динамических требований к транспортному средству с обеспечением оптимальности проектируемых компонентов по критериям минимума габаритов, массы и цены, максимума КПД, с учетом ограничений со стороны силовой электроники, ДВС, остальных частей трансмиссии транспортного средства. Приводятся примеры реализации КТЭО различных транспортных средств, созданных в концерне РУСЭЛПРОМ.

The comprehensive approach of design of all parts of a set of traction electric equipment (STEE) for electromechanical transmissions of various vehicles - generators, traction engines, power and control electronics is considered. Design is carried out for implementation of traction and dynamic requirements to a vehicle with providing an optimality of projected components by criteria of a minimum of dimensions, masses and the prices, an efficiency maximum, taking into account restrictions from power electronics, ICE, other parts of transmission of a vehicle. Examples of realization of STEE of the various vehicles created in concern Ruselprom are given.
Design technique hauling electrical equipment for electromechanics transmissions
Keywords: тяговый электропривод; силовые преобразователи; генераторы; тяговые двигатели; traction electric drive; power converters; generators; traction motors